China trade prospects and U.S. policy - Cohen, Jerome Alan.; Dernberger, Robert F.; Garson, John R.; National Committee on United States-China Relations (New York : Published for the National Committee on United States-China Relations by Praeger, 1971)
This text explores the trade policy between the US and China with a prospect for more future collaboration.
Includes bibliographical references.
ijb 14/01/2019
Loans
Keywords: International Commerce; Trade polcy; United States; China